Analisis Hambatan Belajar Mahasiswa Pada Mata Kuliah Biostatistik - Wetty Mayanora Mendrofa; Grace Putri Laia (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2022)
Education is guidance or assistance provided with the aim that students are responsible for carrying out tasks. Efforts to maximize these activities can be started by minimizing learning barriers. Learning barriers are obstacles that slow down the focus of effort in receiving knowledge. So that the teacher will be right to decide on the learning strategy, thus students are expected to be able to catch up because of these obstacles. This research is classified as a qualitative descriptive study that seeks to describe the analysis of student learning barriers. The subjects in this study were second semester students in the 2021-2025 Health Information Management Study Program, Elisabeth STIKes Medan, who took the Biostatistics course. This study seeks to understand the obstacles experienced by students and uncover things that are considered as factors that hinder student learning in the Biostatistics course. In this study, researchers collected information through diagnostic tests and interviews with students. The results of the analysis show that the obstacles for students in studying Biostatistics generally lie in their basic abilities, namely weak concepts. The results of research conducted by researchers are errors in process skills, errors in understanding questions, and errors in using notation. As an alternative to overcome these obstacles, it is necessary for Biostatistics eye teachers to be able to develop learning strategies so that students can further hone their thinking skills and teachers to be able to provide varied practice questions to students continuously.